Effect of summer outdoor temperatures on work-related injuries in Quebec (Canada). Issue 5 (24th January 2015) - Adam-Poupart, Ariane; Smargiassi, Audrey; Busque, Marc-Antoine; Duguay, Patrice; Fournier, Michel; Zayed, Joseph; Labrèche, France
Abstract : Objective: To quantify the associations between occupational injury compensations and exposure to summer outdoor temperatures in Quebec (Canada). Methods: The relationship between 374 078 injuries compensated by the Workers' Compensation Board (WCB) (between May and September, 2003–2010) and maximum daily outdoor temperatures was modelled using generalised linear models with negative binomial distributions. Pooled effect sizes for all 16 health regions of Quebec were estimated with random-effect models for meta-analyses for all compensations and by sex, age group, mechanism of injury, industrial sector and occupations (manual vs other) within each sector. Time lags and cumulative effect of temperatures were also explored. Results: The relationship between daily counts of compensations and maximum daily temperatures reached statistical significance for three health regions. The incidence rate ratio (IRR) of daily compensations per 1°C increase was 1.002 (95% CI 1.002 to 1.003) for all health regions combined. Statistically significant positive associations were observed for men, workers aged less than 45 years, various industrial sectors with both indoor and outdoor activities, and for slips/trips/falls, contact with object/equipment and exposure to harmful substances/environment. Manual occupations were not systematically at higher risk than non-manual and mixed ones. Conclusions: This study is the first to quantify the association between work-related injury compensations and exposure to summer temperatures according to physical demands of the occupation and this warrants further investigations. In the context of global warming, results can be used to estimate future impacts of summer outdoor temperatures on workers, as well as to plan preventive interventions.